Intellectual developmental disorder with hypertelorism and distinctive facies (IDDHDF) A case study with literature review - Nget, Kimseang; Min, Zhu (Journal of Health Science and Medical Therapy, 2024)
The research aims to investigate the clinical manifestations of neurodevelopmental problems in children with different facies and CCNK gene mutant characteristics. A literature study was carried out to identify the role of CCNK mutations in IDDHDF. Chinese and international search engines like PubMed, MEDLINE, Wanfang Data Knowledge, and Google Scholar were used to search. The search phrases "CCNK", "intellectual developmental disorder", "hypertelorism", and "distinctive facies" were used. A total of 5 studies were found, 11 cases were presented, 3 were thoroughly discussed, and 1 case was presented in this study. The clinical signs and genetic characteristics of children with intellectual developmental disorders with hypertelorism and unique facies were summarized. A male child was 1 year 4 months old. Last 1 year, he appeared of motor and cognitive lag, unable to crawl or stand. He had a large forehead head, wide eye spacing, and cognitive deficiencies, and he was clinically diagnosed with global developmental delay. C.437(exon5) T>C was not found in any of the child's parents and represents a de novo mutation. The main clinical signs were impairments in intellectual development, wide eye spacing, and facial feature features. The findings of the studies discussed here imply that mutations in the CCNK gene may cause IDDHDF. This is a very new kind of study in China to uncover the clinical aspects of a case of Intellectual developmental disorder with hypertelorism and distinctive facies (IDDF). It's discovered that wild-type mRNA coding CCNK partially repaired early defects but not the mRNA with the identified likely pathogenic variation c.331A>G. This shows that CCNK variations are involved in IDDF. The researchers also discovered that the likely pathogenic mutation c.331A>G may induce IDDF via a haploinsufficiency mechanism.